Digitalisasi Ideologi: Mediatisasi Hegemoni Ritual Rambu Solo di Media Sosial - Handayani, Rivi; Ahimsa-Putra, Heddy Shri; Budiman, Christian (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2020)
This article argues that the emergence of contents related to the Rambu Solo ritual on social media is a manifestation of the hegemonic ideology that was digitalized by the new generation of Toraja. Using the theoretical framework of mediatization, this article aims to explore how the hegemony of Rambu solo ritual operates in social media context. By using virtual ethnography method, it can be explained that the mediatization of the hegemony of Rambu Solo rituals on social media are basically implying three things; firstly, the narrative about the Rambu Solo ritual on social media has given birth to a new form of interaction and communication in a broader scope; secondly, the narrative of Rambu Solo ritual on social media has made the media as a new domain to find meanings about the Rambu Solo ritual; and third, the narrative of Rambu Solo ritual indicates the accommodation efforts of the Torajanese new generation towards the rules that apply in the context of social media with the general characteristics of user-generated content. The Torajanes new generation has voluntarily